Utilisation of Powtoon Platform as Learning Media and Improving Student Achievement - Suprapmanto, Joko; yathroh, Isry Laila; Handayani, Fitriah; Sari, Nena Puspita; Salwa, Salwa (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2024)
The development of information technology is increasingly advanced, the world of education should also be able to see opportunities that can be utilized to support the learning process. Powtoon is one of the applications used to do online presentations using interesting animation features such as handwriting animation, cartoons, livelier transitions, and simpler time line arrangements. The purpose of this study was to determine the benefits of the powtoon platfroom as a learning media and improve student achievement. This research uses quantitative research with a survey model, survey tools using google from. The results of this study explain that powtoon can be made as a learning media with interesting features, so that it can increase student understanding in learning. The conclusion of this study explains that the benefits of the powtoon platform as a learning media are very effective for teachers to use in a more effective learning process so that it can improve student achievement. The limitation of this study is that researchers only utilize the powtoon application as a platform to improve student achievement, therefore further research should be able to conduct research aimed at developing the powtoon application as a learning media that can increase student motivation, enthusiasm and activeness in discussions.